Adsorption of CO on C,N–TiO Surfaces - Magdalena Janus (Adsorption Science & Technology)
Modification of the TiO 2 surface by carbon and nitrogen results in the formation of photocatalysts that have high sorption capacity for CO 2 . The photocatalysts were obtained as follows: approximately 1 g of bare TiO 2 was placed in a furnace and kept for 1 hour at a temperature from 100 to 600 °C. The sample was first placed under argon atmosphere, following which it was placed under an atmosphere of carbon and nitrogen, achieved by passing ammonia via a washer with n-hexane. This treatment is continued for 1 hour, following which the sample was cooled down to room temperature under argon atmosphere. The photocatalysts thus obtained were characterized by Fourier transform-infrared/diffuse reflectance spectroscopy, UV–Vis/diffuse reflectance, X-ray diffraction and Brunauer, Emmett and Teller surface area measurements. In addition, the zeta potential of the surface of photocatalysts was measured. Sorption tests were conducted in a special reactor using the following conditions: temperature: 20 °C, gas flow rate: 100 cm 3 /minute; CO 2 concentration: 1000 ppm. Our results show that the best sorbent was TiO 2 modified at 100 °C for 1 hour. Its sorption capacity amounted to 6.63 mg of CO 2 on 1 g of C,N–TiO 2 photocatalyst.